The Relationship Between Food Consumption Diversity and Maternal Parenting Patterns with Stunting in Toddlers - Noni Humaira; Vaulinne Basyir; Arni Amir; Delmi Sulastri; Mayetti -; Yusrawati - (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Stunting is malnutrition in toddlers, especially in the first 1000 days of life, which causes stunted physical growth and susceptibility to disease. Stunting is one of Sustainable Development Goals (SDGs) targets in the 2nd sustainable development goal with the target set is to reduce the stunting rate by 40% in the year 2025. According to Minister of National Development Planning (2020), Padang is one of cities for integrated stunting reduction interventions in 2021. The highest prevalence of stunting in Padang Selatan District occurred in Seberang Padang Health Center working area, which is 16.4%. In 2021, the prevalence of stunting in the Puskesmas Seberang Padang working area increased to 17.8% of the total 590 toddlers whose height was measured. This study aims to determine the relationship between food consumption diversity and maternal parenting with the incidence of toddlers' stunting in the working area of Puskesmas Seberang Padang. This research was conducted by observational study using cross-sectional design. The study population was all toddlers in Seberang Padang Health Center’s work area with sample of 179 respondents using proportional sampling as sampling technique and collected by questionnaire. The result showed that food consumption diversity (p=0.000), food parenting (p=0.000), hygiene parenting (p=0.026), health parenting (p=0.018) and psychosocial stimulation parenting (p=0.031) have significant relationship with the incidence of stunting. The most dominant factor is food consumption diversity (OR=24,263). The conclusion of this study is that there is significant relationship between the diversity of food consumption, food parenting, hygiene parenting, health parenting and psychosocial stimulation parenting with the incidence of stunting and the most dominant factor is the diversity of food consumption.Keywords: Food consumption diversity, Maternal parenting pattern, Stunting